A Resonance Tube Coupled Duplex Stirling Cooler. (May 2017) - Li, Xiaowei; Liu, Bin; Yu, Guoyao; Dai, Wei; Hu, Jianying; Luo, Ercang; Li, Haibing
Abstract: In comparison with the classical duplex Stirling cooler, this paper puts forward a resonance tube coupled duplex Stirling cooler, which uses a simple resonance tube to match the impedance between the engine and the cooler. The new system promises advantages of high exergy efficiency, high reliability and flexibility in application. Therefore, it is attractive for some applications such as natural gas liquefaction and long lifetime space coolers. Based on an off-the-shelf prototypes in our laboratory, a calculation model has been built based on commercial software Sage, through which considerable quantitative analyses have been done. Then, according to the calculation, experiments were carried out and a no-load temperature of 110 K has been obtained, which effectively validates this innovative configuration.